Maternal protein restriction affects fetal ovary development in sheep - Chinwe U Nwachukwu; Kathryn J Woad; Nicole Barnes; David S Gardner; Robert S Robinson (Bioscientifica, 2021)
Maternal malnutrition has important developmental consequences for the foetus. Indeed, adverse fetal ovarian development could have lifelong impact, with potentially reduced ovarian reserve and fertility of the offspring. This study investigated the effect of maternal protein restriction on germ cell and blood vessel development in the fetal sheep ovary. Ewes were fed control (n = 7) or low protein (n = 8) diets (17.0 g vs 8.7 g crude protein/MJ metabolizable energy) from conception to day 65 of gestation (gd65). On gd65, fetal ovaries were subjected to histological and immunohistochemical analysis to quantify germ cells (OCT4, VASA, DAZL), proliferation (Ki67), apoptosis (caspase 3) and vascularisation (CD31). Protein restriction reduced the fetal ovary weight (P < 0.05) but had no effect on fetal weight (P > 0.05). The density of germ cells was unaffected by maternal diet (P > 0.05). In the ovarian cortex, OCT4+ve cells were more abundant than DAZL+ve (P < 0.001) and VASA+ve cells (P < 0.001). The numbers, density and estimated total weight of OCT4, DAZL, and VASA+ve cells within the ovigerous cords were similar in both dietary groups (P > 0.05). Similarly, maternal protein restriction had no effect on germ cell proliferation or apoptotic indices (P > 0.05) and the number, area and perimeter of medullary blood vessels and degree of microvascularisation in the cortex (P > 0.05). In conclusion, maternal protein restriction decreased ovarian weight despite not affecting germ cell developmental progress, proliferation, apoptosis, or ovarian vascularity. This suggests that reduced maternal protein has the potential to regulate ovarian development in the offspring.